The Methods of Contemporary Thought - Bochenski, J.M. author. aut Link
145 p.
Keywords: Professor Bochenski, as he himself points out in the prologue, is a logician; he is best known in England and the United States for his work in the history of logic, and more recently in Soviet and East European philosophy. But he has taught philosophy for many years - in Rome, in Switzerland, and on a number of visits to the United States - and in this book provides an elementary introduction to contemporary work in the field. As a means to this end he has chosen to deal with four alternative methods employed by philosophers in the twentieth century. Philosophical methodology has not attracted much attention, in English speaking circles, as a distinct branch of the discipline of philosophy; the term "methodologist", if used at all, would ordinarily be taken to refer to somebody concerned with scientific rather than philosophical method. When, therefore, Professor Bochenski refers, as he frequently does, to "contemporary methodologists", meaning people who debate the re spective merits of phenomenology and mathematical logic as ways of approaching the world, the phrase has an odd ring. But philosophical methodology really makes a great deal more sense than scientific method ology. In science methodology is almost superfluous; given all the avail able information and a reasonably clear idea of what is wanted, there is usually not much ambiguity as to the means of getting it, or not much that could be resolved by mere argument.